European Financial Market Integration: A Closer Look at Government Bonds in Eurozone Countries - Sebastian Weber (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The European Union made a number of steps not least of them the introduction of a common currency to foster the integration of the European financial markets. A number of papers have tried to gauge the degree of integration for various financial markets looking at the convergence of interest rates. A common finding is that government bond markets are quite well integrated. In this paper stochastic Kernel density estimates are used to take a closer look at the dynamics that drive the process of interest rate convergence. The main finding is that countries with large initial deviations from the mean interest rate do indeed converge. Interestingly the candidates least suspected namely the countries initially with interest rates at the mean level show a pattern of slight divergence.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: C23; E44; G15; 330; Financial markets integration; euro area government bonds; stochastic Kernel density estimates